INTEGRASI SOSIAL PETANI RUMPUT LAUT DALAM MENINGKATKAN POLA HIDUP (STUDI DI DESA NAIN SATU KECAMATAN WORI KABUPATEN MINAHASA UTARA) - Saadia, Efen; Lesawengen, Lisbeth; Zakarias, Jhon D. (HOLISTIK, Journal Of Social and Culture, 2020)
Seaweed is one of the most promising efforts if it can be managed intensively. From the research showed that the process of seaweed management developed by the community, especially in the village NainI when developed intensively. Until now, the community has been integrated to develop seaweed cultivation by utilizing enough potential sea water, so that it has a good enough prospects in the development of community life patterns. It has been understood that the process of community integration in the handling of seaweed cultivation, especially in the village of Nain Satu until now, among others, is done with the following stages: a). By means of location selection/maintenance and utilization of seedlings B). Location selection cultivation and the method of manufacture C). Planting process and breeding seaweed D). Seedlings care and Maintenance system e). Process of handling post Panen f). Profit gained from the management of Seaweed g). Impact on increase in farmer income h). Improvement in life patterns. With the management of seaweed cultivation is still encountered constraints that affect the life of the community, the control between through: a). Seeds of disease a). Imperfect post-harvest treatment. c). Storage process D). Transportation process. e). Fluctuating price fluctuationsÂ Keywords: social integration, seaweed farmer, life pattern